Gas Diffusion and Sorption in Carbon Conversion. (February 2019) - Wedler, Carsten; Arami-Niya, Arash; Xiao, Gongkui; Span, Roland; May, Eric F.; Richter, Markus
Abstract: In common carbon conversion models, effective diffusion is considered to describe mass transport of reactive gases in porous char particles. Conventionally, effective diffusion is determined by taking porosity and tortuosity of the solid char into account, however, the tortuosity cannot be determined experimentally. Therefore, values for the tortuosity are mainly chosen to fit the respective model to experimental data. Here, we present the determination of effective diffusion by measuring the sorption kinetics utilizing a volumetric sorption analyzer to circumvent the problem of obtaining proper data for tortuosity. For this purpose, sorption kinetics were determined for carbon dioxide and methane at temperatures of (25 and 50) °C and pressures up to 115 kPa in a synthetic lignite-like solid fuel.